Homology modelling and structural analysis of phyFAUIA1_H and Bacillus subtilis ASUIA243 phytases - Noorbatcha, Ibrahim Ali; Sultan, Anas Mufid Nasri; Amid, Azura; Mohd. Salleh, Hamzah (Research Journal of Chemistry and Environment, 2010)
Homology modeling is a powerful tool in predicting the three dimensional (3D) structure of a protein using a solved structure within the same family as template. Compared to other methods such as X-ray crystallography and NMR, homology modelling has the advantage of being a fast yet reliable technique in solving proteins’ 3D structures, starting from their amino acid sequences. In this study, homology modelling was used to obtain the 3D structure of two different phytases using only their amino acid sequence; phyFAUIA1_H which belongs to the histidine acid phosphatases and Bacillus subtilis ASUIA243 which belongs to the β-propeller phytases. E. coli phytase (PDB code 1dkm) was used as a template for phyFAUIA1_H model with 99.512% sequence identity. On the other hand, Bacillus amyloliquefaciens (PDB code 2poo) was used as a template for B. subtilis ASUIA243 model with 71.268% sequence identity. Both models were evaluated and found to be quite satisfactory without being manually modified. These models can now be used in protein structural studies to improve properties such as specific activity, pH tolerance and thermostability.